Uzhcurrumi: estrategia de comunicación para promoción del turismo rural - Encalada Guartazaca, Christian Xavier; Gonzabay Peralta, Leonardo Adrian (Machala, 2022)
This research systematizes the experience of putting communication actions into practice as a strategic tool for promoting nature-based tourism, carried out in the rural parish of Uzhcurrumi in Ecuador. A diagnosis of the tourist attractions of the sector was carried out, with which strengths, weaknesses, threats and opportunities of the context were determined, through interviews with key actors in situ. This made it possible to have the necessary elements for the design and execution of an express tourism promotion campaign in a specific audience, in this case a small group of students from the Carmen Mora de Encalada High School, in the city of Pasaje, who were initially surveyed, then they were trained in their own educational entity, to later transfer them to live the experience in situ in the rural parish, where they learned about the wealth of flora and fauna, gastronomy, practiced extreme sports and shared with natives of the community. The visiting students were co-creators of content for social networks and became promoters of the dissemination of tourism; always guided by tourism and communication specialists. These results were evaluated through scientific research techniques and instruments. With the respective monitoring and evaluation of the final phase, it is concluded that the best way to promote nature-based tourism is the narrative experience, where the visitor becomes an effective promoter of the rural sector that he has known. The systematization of this communicational experience was documented as part of the titling work and is important for the projection of this rural area of ​​Ourense as a rural tourist destination, based on the conservation of natural resources and experiential experiences.
La presente investigación sistematiza la experiencia de la puesta en práctica de acciones de comunicación como herramienta estratégica para la potenciación del turismo basado en la naturaleza, ejecutado en la parroquia rural Uzhcurrumi de Ecuador. Se realizó un diagnóstico de los atractivos turísticos del sector, con lo que se determinaron fortalezas, debilidades, amenazas y oportunidades del contexto, a través de entrevistas con actores claves in situ. Esto permitió tener elementos necesarios para el diseño y ejecución de una campaña express de promoción turística en una audiencia determinada, en este caso a un grupo pequeño de estudiantes del Colegio de Bachillerato Carmen Mora de Encalada, de la ciudad de Pasaje, a quienes se los encuestó inicialmente, luego se los capacitó en su misma entidad educativa, para después trasladarlos a vivir la experiencia in situ en la parroquia rural, donde conocieron la riqueza de flora y fauna, la gastronomía, realizaron deportes extremos y compartieron con oriundos de la comunidad. Los estudiantes visitantes fueron co creadores de contenidos para redes sociales y se convirtieron en promotores de la divulgación del turismo; siempre guiados por especialistas de turismo y de comunicación. Se evaluaron estos resultados, a través de técnicas e instrumentos de investigación científica. Con el monitoreo respectivo y la valoración de la fase final, se concluye que la mejor forma de promocionar el turismo basado en la naturaleza es la narrativa experiencial, donde el visitante se convierte en promotor efectivo del sector rural que ha conocido. La sistematización de esta experiencia comunicacional fue documentada como parte del trabajo de titulación y es importante para la proyección de esta zona rural orense como destino turístico rural, basado en la conservación de los recursos naturales y las vivencias experienciales.
Keywords: TURISMO RURAL; COMUNICACION; PROMOCION TURISTICA RURAL